Spotlight on Mobocertinib (TAK-788) in NSCLC with EGFR Exon 20 Insertion Mutations - Zhang SS; Zhu VW (Lung Cancer: Targets and Therapy, 2021)
Shannon S Zhang,1 Viola W Zhu1,2 1University of California, Irvine School of Medicine, Department of Medicine, Orange, CA, USA; 2Chao Family Comprehensive Cancer Center, Orange, CA, USACorrespondence: Viola W ZhuUniversity of California, Irvine School of Medicine, Department of Medicine, 200 S Manchester Ave, Suite 410, Orange, CA, 92868, USATel +1 714-456-8105Fax +1 714-456-2242Email zhuvw@hs.uci.eduAbstract: The EGFR exon 20 insertion (EGFRex20ins) mutations are the third most common EGFR mutations seen in non-small cell lung cancer (NSCLC). More than 50 variants of EGFRex20ins mutations have been identified with A767_V769dupASV being the most common variant across multiple surveys. Treatment with currently available EGFR tyrosine kinase inhibitors (TKIs) including osimertinib is generally ineffective. Amivantamab (JNJ-372), a bispecific monoclonal antibody against EGFR and MET, has recently been approved by the US FDA for patients with advanced or metastatic NSCLC harboring EGFRex20ins mutations after disease progression on platinum-based chemotherapy. Among all the TKIs in clinical development, mobocertinib (TAK-788) has been granted priority review by the FDA for the same indication as amivantamab. Here, we provide a concise review on mobocertinib, with a focus on its chemical structure, preclinical data, and phase 1/2 trial results. Future directions will likely focus on combination approach such as TKI plus chemotherapy in the first-line setting, designing drugs with CNS activity, and exploring disease characteristics of various EGFRex20ins mutation variants and how they may affect treatment response.Keywords: mobocertinib, TAK-788, NSCLC, EGFR exon 20 insertion, TKI, amivantamab